Nonlinear geometric model of structure of the ensemble antigraviting galaxies - Zhanabaev, Z.Zh.; Khokhlov, S.A. (Recent Contributions to Physics, 2015)
In this paper used a new authors` idea about the behavior of a physical quantity near its critical value as non-linear fractal measure to describe the geometric arrangement of galaxies. As a critical distance from the viewpoint taken the size of the Local galaxies group and the distance of zero gravity. This approach to the problem of cosmology different from other modern studies in that easiest way is realized basic idea of the general relativity theory - relationship between structures of space and distribution of matter. Obtained equation that describes deviation of the sizes galaxies as a fractal measure of the distance, measured from the center of Local galaxies Group. “Speed – distance” diagram is constructed. Up to a zero gravity distance velocities of galaxies can be both, positive and negative, then – speed can be described on the Hubble law. Comparison the theory with observations shows lawfulness of the main provisions at the proposed theory.